Analisis Perbedaan Prestasi Kerja Dan Kepuasan Kerja Ditinjau Dari Tingkat Pendidikan Karyawan Divisi Umum Dan Sumber Daya Manusia PT. Inalum, Kuala Tanjung - Elisabeth Siahaan; Leonard Sagala (JURNAL AGRICA, 2018)
This research was aimed to know the difference of Work Performance level and the difference of Work Satisfaction within employees who have different level of education in General Affair and Human Resources Division of Inalum Co, Ltd. Kuala Tanjung. The variables are work Performance, Work Satisfaction, and employee’s Level of Education. Was done to employees of General Affair and Human Resource Division of Inalum Co, Ltd. Kuala Tanjung and used Proportionate Stratified Random Sampling Method.   The primer data of this research’s got from questionnaires and interview and used Likert Scale in measuring method. The data’s analyzed statistically by using SPSS 14.0 for windows program such as Classic Assume Test, Homogenity of Varian Test, Analysis of Varian, and described the respondences’ perceptions in the questionnaires descriptively.            From the result of this research, We know the F distribution value of Work Performance variable is 1,913 points. It is lower than Ftable distribution value which means that there’s no significant difference of Work Performance within employees who have different Level of Education. Where as the F distribution value of Work Satisfaction variable is 16,484 points which is higher than Ftable distribution value. This means that there is difference of Work Satisfaction within employees who have different Level of Education. Keywords: Work Performance, Work Satisfaction, Level of Education